2000
DOI: 10.1002/14651858.cd002760
|View full text |Cite
|
Sign up to set email alerts
|

Single dose oral dihydrocodeine for acute postoperative pain

Abstract: Background This is an updated version of the original Cochrane review published in Issue 2, 2000. Dihydrocodeine is a synthetic opioid analgesic developed in the early 1900s. Its structure and pharmacokinetics are similar to that of codeine and it is used for the treatment of postoperative pain or as an antitussive. It is becoming increasingly important to assess the relative efficacy and harm caused by different treatments. Relative efficacy can be determined when an analgesic is compared with control under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…The resultant NNT was 6, far worse than available for drugs in Table 1, and far worse than ibuprofen 400 mg in the only direct comparison. 6 The Cochrane overview concluded that the results for dihydrocodeine were not robust because of the smallness of the data set available, and that unpublished results from just 46 patients in zero effect trials would be needed to make any result clinically irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant NNT was 6, far worse than available for drugs in Table 1, and far worse than ibuprofen 400 mg in the only direct comparison. 6 The Cochrane overview concluded that the results for dihydrocodeine were not robust because of the smallness of the data set available, and that unpublished results from just 46 patients in zero effect trials would be needed to make any result clinically irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence showing that paracetamol plus codeine combinations are effective in acute pain (Toms 2009), but limited evidence for cancer pain . Dihydrocodeine was not effective in acute postoperative pain (Moore 2000), and there is very little evidence on its efficacy in other pain conditions. Codeine is not effective in acute postoperative pain (Derry 2010).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…It plays a role in the treatment of moderate, chronic pain as well as cough, diarrhoea, and opioid addiction [30,31]. DHC displays superior analgesia, less fatigue, sleep disturbance, nausea, and vomiting, and better appetite in comparison to tramadol [32]. In some studies, single 30 mg and 60 mg doses of DHC did not provide desirable analgesia in postoperative pain whereas 400 mg ibuprofen provided statistically superior analgesia [33].…”
Section: Opioids In a Nutshell And Controversies Surrounding The Use mentioning
confidence: 99%
“…Odgrywa ona rolę w leczeniu umiarkowanego, przewlekłego bólu, a także kaszlu, biegunki i uzależnienia od opioidów [30,31]. Charakteryzuje się lepszą analgezją, zmniejszonymi objawami: zmęczenia, zaburzeń snu, nudności, wymiotnymi, oraz lepszym apetytem w porównaniu z tramadolem [32]. W niektórych badaniach pojedyncze dawki 30 mg i 60 mg dihydrokodeiny nie zapewniły pożądanej analgezji w bólu pooperacyjnym, natomiast ibuprofen w dawce 400 mg zapewniał analgezję statystycznie lepszą [33].…”
Section: Opioidy "W Pigułce" I Kontrowersje Wokół Stosowania Wybranycunclassified